Growth and reproduction of the mangrove crab Goniopsis cruentata (Latreille, 1803) (Crustacea: Decapoda: Grapsidae) in southeastern Brazil - Carla R.G. Reis; Fabiano G. Taddei; Valter J. Cobo (Anais da Academia Brasileira de Ciências, 2015)
Goniopsis cruentata is a common semi-terrestrial crab in Brazilian mangroves and an important fishery resource for traditional communities in the northeastern Brazilian coast. Aiming to contribute to the knowledge about the species, this study evaluated the carapace width and weight growth curves, the relative growth of weight versus carapace width, and the temporal variation of gonadosomatic and hepatosomatic indices for the species. A total of 524 crabs were collected in a mangrove area of Ubatuba municipality, state of São Paulo. The growth-curves parameters and longevity (tmax) were estimated for males (CW∞=50.6 mm, WE=56.4 g, k=2.24, t0=0.003631502 year-1, tmax=1.3 years) and females (CW∞=50.7 mm, WE∞=58.8 g, k=2.50, t0=0.003247209 year-1, tmax=1.2 years). The age at onset of sexual maturity was 0.23 years for both genders. The weight-growth model was isometric for the immature developmental stages and allometric negative for adults. The species exhibited a continuous reproduction, with breeding peaks in spring and summer months. The weight dynamics of gonads and hepatopancreas were not clearly related. The growth and reproductive patterns indicated that Goniopsis cruentata has a life-history that prioritizes reproduction instead of survival. The species exhibited some of the highest growth rates and lowest longevity estimates reported for brachyuran species in Brazil.